Treatment of high-risk gestational trophoblastic neoplasia and chemoresistance/relapsed disease. (July 2021) - Braga, Antonio; Elias, Kevin M.; Horowitz, Neil S.; Berkowitz, Ross S.
Abstract: High-risk gestational trophoblastic neoplasia (GTN) has an increased risk of developing chemoresistance to single-agent chemotherapy; therefore, the primary treatment should be a multiagent etoposide-based regimen, preferably EMA/CO. After remission (normalization of human chorionic gonadotropin – hCG), at least three consolidation courses of EMA-CO are needed to reduce the risk of relapse. Chemoresistance is diagnosed during treatment if hCG levels plateau/increase, in two consecutive values over a two-week period. When this occurs after remission, in the absence of a new pregnancy, there is a relapse. In both cases, after re-assessment of the extent of disease, EMA-EP is the most common chemotherapy choice. Even in these cases, remission rates are high. After remission is achieved, hCG should be measured monthly for a year. Pregnancy can be allowed after 12 months from remission. The follow-up of these patients in referral centers minimizes the chance of death from this disease and should be encouraged. Highlights: Even with widespread metastases, high-risk GTN is still curable. High-risk GTN should be treated with multiagent regimens. EMA/CO is the current regimen of choice in high-risk GTN. Surgery may be indicated in cases of chemoresistance in high-risk GTN.